GAMBARAN PERILAKU ACADEMIC SELF-HANDICAPPING PADA SISWA SMP DI KEPULAUAN SELAYAR - Fitri, Nur Madani; Aryani, Farida; M. Amirullah; Sinta Nurul Oktaviana Kasim (IKIP Siliwangi, 2026)
Academic self-handicapping is a critical issue as it may hinder students’ academic achievement and personal development. This study aimed to describe the tendency of such behavior among junior high school students. A quantitative descriptive approach was employed. The participants consisted of 83 students who completed an academic self-handicapping questionnaire. Data were analyzed using descriptive statistics by categorizing scores into very high, high, moderate, and low levels, and by mapping them into behavioral and claimed self-handicapping dimensions. The findings revealed that 7 students (9%) were in the very high category, 39 students (47%) in the high category, 31 students (37%) in the moderate category, and 6 students (7%) in the low category. In terms of behavioral forms, 48 students (58%) predominantly exhibited behavioral self-handicapping, while 35 students (42%) showed greater tendencies toward claimed self-handicapping. These results indicate a relatively high level of self-handicapping, primarily expressed through observable behaviors that may negatively affect academic performance. The findings highlight the importance of guidance and counseling interventions to promote more adaptive learning strategies